Is Tax Coordination a Solution of Trade Distortions in SACU? Possibilities for Coordination of Value Added Tax in the Southern African Customs Union - Letete, Puseletso (Comparative and International Law Journal of Southern Africa, 2022)
With the rise of regional integration and increasing globalisation, member countries to regional organisations and trading blocs, are under pressure to strengthen their economic integration. In view of this move, this paper explores the importance of extending this integration towards areas of Value Added Tax systems within the Southern African Customs Union. The paper argues that coordination of Value Added Tax within SACU will be beneficial for purposes of forging closer economic integration. This will also contribute towards fostering intra-regional trade between member states as well as in addressing issues of trade distortions which are caused by different VAT legal systems.